Native Valve Endocarditis due to Veillonella Species: A Case Report and Review of the Literature - Lakshmi Saladi; Cosmina Zeana; Manisha Singh (Case Reports in Infectious Diseases)
Veillonella species are fastidious bacteria that have been isolated from skin, dental, and respiratory tract infections and rarely have been implicated in serious infections like meningitis, endocarditis, and osteomyelitis. A 76-year-old woman presented to our hospital with fever, vomiting, and generalized weakness for 3 days. A transthoracic echocardiogram showed a mobile structure on anterior mitral valve leaflet measuring 0.9 cm suggestive of vegetation. Empiric therapy with vancomycin and piperacillin-tazobactam was started with clinical resolution of her symptoms. On day 6, the blood culture drawn at admission grew Veillonella species. A transesophageal echocardiogram confirmed a 1.2 × 0.4 cm echo dense structure attached to the left ventricular side of the anterior mitral leaflet. The patient was discharged home after 10 days of inpatient antibiotic therapy and completed 4 weeks of IV ceftriaxone at home without any adverse events. She was reevaluated in the clinic after completion of treatment and repeat blood cultures remained negative. We report the first case of successful treatment of endocarditis due to Veillonella species with once daily ceftriaxone.